The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00216-020-03143-0
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation, and application of a quantitative volumetric absorptive microsampling–based method in finger prick blood by means of LC-HRMS/MS applicable for adherence monitoring of antipsychotics

Abstract: Volumetric absorptive microsampling (VAMS), an emerging microsampling technique, is expected to overcome some disadvantages of dried blood spots such as volume inaccuracy and influence of hematocrit (HT). This study aimed to develop and evaluate a VAMS-based strategy for quantification of 13 frequently prescribed antipsychotics in finger prick blood within the scope of adherence monitoring to complement already-established qualitative urine analysis. The final workflow consisted of VAMS tip hydration and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…All other analytes met recommended criteria for accuracy and precision [35]. The advantage of the zero sample compared to the precipitation agent spiked with IS for the dilution of the final extract was shown in previous studies [26,27]. Including the dilution factor, the upper part of the therapeutic range of canrenone and torasemide can be covered.…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…All other analytes met recommended criteria for accuracy and precision [35]. The advantage of the zero sample compared to the precipitation agent spiked with IS for the dilution of the final extract was shown in previous studies [26,27]. Including the dilution factor, the upper part of the therapeutic range of canrenone and torasemide can be covered.…”
Section: Methods Validationmentioning
confidence: 99%
“…S1). VAMS were already used for e.g., screening procedures in different matrices, metabolic studies, therapeutic drug monitoring, and adherence monitoring [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Haloperidol was stable for 7 days, whereas amisulpride, aripiprazole, clozapine, paliperidone, pipamperone, quetiapine, and risperidone were stable for 2 weeks. 98 Similarly, Velghe et al reported that VAMS specimens were acceptable for the monitoring of 4 antiepileptics, carbamazepine, valproic acid, phenobarbital, and phenytoin. VAMS stored at room temperature, 48C, and 2208C were stable for one month, and when stored at 608C, for 7 days.…”
Section: Volumetric Absorptive Microsamplingmentioning
confidence: 99%
“…Advanced dried sample devices collect samples as a fluid and produce a dried sample either with a polymer tip (volumetric absorptive microsampling, "VAMS"-Neoteryx; Torrance, CA, USA) or carriers akin to DBS cards, such as the hemaPEN (Trajan; Melbourne, VIC, Australia), HemaXis DB10 (DBS System SA; Gland, Switzerland), Capitainer qDBS (quantitative dried blood spot) and B-Vanadate (Capitainer AB; Solna, Sweden), TASSO-M20 (HemoLink; Seattle, WA, USA), and HemaSpot HD and HF (Spot on Sciences; San Francisco, CA, USA) [27,28,36,[66][67][68][69][70][71][72][73]. These technologies improve upon standard DBS cards by providing accurate/volumetric aspiration and thus heamatocrit-independent sample collection over a wide range of microsample sizes (2.74-30 µL).…”
Section: Approaches To Microsample Collectionsmentioning
confidence: 99%